2011
DOI: 10.1155/2011/304960
|View full text |Cite
|
Sign up to set email alerts
|

Antispasmodic and Antidiarrheal Activities of Valeriana hardwickii Wall. Rhizome Are Putatively Mediated through Calcium Channel Blockade

Abstract: Valeriana hardwickii is indigenous to Pakistan, Burma and Ceylon, where it is traditionally being used as an antispasmodic and antidiarrheal, besides its culinary use as spice. The aim of this paper was to provide pharmacological validation to these medicinal uses. The crude aqueous-methanolic extract of Valeriana hardwickii rhizome (Vh.Cr) was studied on isolated rabbit jejunum and castor oil-induced diarrhea in mice for spasmolytic and antidiarrheal properties, respectively. Vh.Cr caused concentration-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…It showed a dose-dependent inhibitory effect on spontaneous contractions, thus showing that the observed antidiarrheal effect of the plant extract appears to be mediated through the presence of some gut relaxant component(s) in it. In our earlier studies, we observed that the spasmolytic effect of medicinal plants is usually mediated through K + channel opening (Gilani et al, 2005(Gilani et al, , 2006 or Ca ++ channel blockade (Bashir et al, 2011;Shah et al, 2011a). To assess, whether the spasmolytic effect of the crude extract of S. officinalis was also mediated via similar mechanism(s), it was tested on low K + (25 mM) and high K + (80 mM)-induced contractions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It showed a dose-dependent inhibitory effect on spontaneous contractions, thus showing that the observed antidiarrheal effect of the plant extract appears to be mediated through the presence of some gut relaxant component(s) in it. In our earlier studies, we observed that the spasmolytic effect of medicinal plants is usually mediated through K + channel opening (Gilani et al, 2005(Gilani et al, , 2006 or Ca ++ channel blockade (Bashir et al, 2011;Shah et al, 2011a). To assess, whether the spasmolytic effect of the crude extract of S. officinalis was also mediated via similar mechanism(s), it was tested on low K + (25 mM) and high K + (80 mM)-induced contractions.…”
Section: Discussionmentioning
confidence: 97%
“…To assess the involvement of K + channel opening (Gilani et al, 2006) and Ca ++ antagonist-like mechanisms (Bashir et al, 2011), the spasmolytic effect of the plant extract was tested on low K + (25 mM) and high K + (80 mM)-induced contractions in the isolated rabbit jejunum preparations. Following a sustained contraction in response to K + , the test material was added in a cumulative fashion to obtain the concentration-dependent inhibitory responses.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…The spontaneous contractions of smooth muscles are dependent on increased cytoplasmic calcium levels, in turn activates the contractile elements. While action potential for maximal depolariza -tion is produced through a rapid influx of Ca 2+ via the VDLCs (voltage-dependent L type channels) or released from sarcoplasmic reticulum calcium stores (Brading and Sneddon, 1980;Karaki et al, 1997;Bashir et al, 2011). The decrease in the spontaneous movements of jejunum by crude extract is assumed to be mediated through Ca 2+ channels blockade (Janbaz et al, 2012), as it was earlier observed that the antispasmodic constituents found in various medicinal plants inhibited the Ca 2+ movement to produce their effect (Gilani et al, 2005a(Gilani et al, , 2005b.…”
Section: Discussionmentioning
confidence: 99%
“…The research is being conducted mainly in universities and that too as ethno-botanical listing of resources. Recently the work on various medicinal plants were carried out in various institutes to establish their antimicrobial, antiplatelet and acetylcholinesterase, inhibitory constituents, inflammatory, analgesic, gut modulatory, antidiarroeal effects and constipation effects , 2011, Ahmad and Gilani, 2011, Bashir et al, 2011, Mahmood et al, 2011. …”
Section: Research and Development In Traditional/complementary And Almentioning
confidence: 99%